Analisis Yusuf Qardhawi Tentang Produksi dan Konsumsi Dalam Hukum Islam - Sidiq, Fierda Febrianti; Gausian, Gini (STAI Al Musaddadiyah Garut, 2022)
In the current reality, there has been injustice and inequality in the distribution of income and wealth in both developed and developing countries that use the capitalist system as their economic system, thus creating poverty everywhere. The Islamic worldview includes economics. Islam views the economy as being in the middle and strives for a fair balance in all areas of the economy, including the balance between business and capital, output and consumption, intermediaries between producers and consumers, and social groups. The consumption of a Muslim also needs to be oriented towards compassion and empathy for those who are less powerful and more needy. Because improving oneself also means improving others. The research method in this study uses library research, namely tracing and utilizing library sources to obtain the data needed in research. Research results that Qardhawi argues that this. Keywords: Production, Consumption, Yusuf Qardhawi